Incest Prevention and the Strengthening of Family Resilience from the Perspective of the Prophet's Hadith - Muh Rizki; Septian Fiktor Riyantoro; Ahmad Andri; M Imron; Khairul Akmal (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The phenomenon of incest is a serious issue because it violates mahram boundaries and threatens the safety, honor, and resilience of the family. Changes in family interaction patterns in the digital age also present challenges in the form of exposure to sexual content, unsupervised use of digital devices, and a lack of communication between parents and children. This study aims to analyze incest as a threat to family resilience and to examine the relevance of the hadiths of the Prophet Muhammad, peace be upon him, in establishing moral protection for Muslim families. This study employs a qualitative approach using library research and a thematic (maudhu’i) approach in the analysis of hadiths. Primary sources consist of hadiths from Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Sunan Abī Dāwūd, and other relevant hadith collections, while secondary sources include books, journal articles, and research on incest, family resilience, child protection, digital literacy, and sex education. The data were analyzed through inventory, classification, interpretation, and thematic analysis. The research findings indicate that incest threatens family resilience by undermining the functions of protection, trust, honor, and relationships among family members. The Prophet’s hadiths contain preventive values such as upholding mahram boundaries, honor, and privacy; Islamic-values-based sex education; parental responsibility; child protection; and the internalization of ḥayā’. These values can be reconstructed as a foundation for strengthening family resilience through education, supervision, protection, and the establishment of family moral control